Dragon kingdom of Wrenly. Book 5, Inferno New Year - Quinn, Jordan (Quinn, Jordan. Dragon Kingdom of Wrenly, 2021)
The island of Crestwood's largest volcano erupts and sends Cinder, Groth, and Roke to the palace to stay with Ruskin until it is safe to return, but after the spectacular explosions are finished danger continues to follow the dragons.